Estudo do status sorológico de pacientes com doenças do espectro da neuromielite óptica por meio do desenvolvimento de um nanoimunossensor de nanopartículas de prata - Bueno, Raquel Gurge (Universidade Federal de São Carlos, 2024)
In the current scenario, the diagnosis of neuromyelitis optica spectrum disorders is mainly based on the detection of a specific biomarker, the AQP4-IgG autoantibody, which targets the Aquaporin-4 (AQP4) protein in astrocytes of the Central Nervous System. However, approximately 10 to 27% of patients with clinical evidence of the pathology are classified as seronegative for the presence of the autoantibody in question, according to the test recommended by the International Panel for the Diagnosis of Neuromyelitis Optica, which makes it difficult to diagnose diagnosis and delays treatment. Faced with this challenge, the present work focused on the development of a nanobiosensor using silver nanoparticles functionalized with the AQP461-70 epitope in order to improve the detection rate of AQP4-IgG. As a result of the developed nanobiosensor, a sensitivity of 84,62%, surpassing the conventional approach, but with a specificity rate of 66,67%, indicating the need for future research to improve this aspect of the diagnosis.
Study of the serological status of patients with diseases of spectrum of neuromyelitis optica with development ot a silver nanoparticle nanoimunosensor
Keywords: Neuromielite óptica; Nanobiossensor; Neuromyelitis optica; Nanobiosensor; silver nanoparticles; Nanopartículas de Prata; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR